2013
DOI: 10.1109/tcomm.2013.100913.130232
|View full text |Cite
|
Sign up to set email alerts
|

ALOHA Random Access that Operates as a Rateless Code

Abstract: Various applications of wireless Machine-to-Machine (M2M) communications have rekindled the research interest in random access protocols, suitable to support a large number of connected devices. Slotted ALOHA and its derivatives represent a simple solution for distributed random access in wireless networks. Recently, a framed version of slotted ALOHA gained renewed interest due to the incorporation of successive interference cancellation (SIC) in the scheme, which resulted in substantially higher throughputs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
156
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(157 citation statements)
references
References 23 publications
1
156
0
Order By: Relevance
“…This comes from the inherent nature of SIC where suddenly a large number of users' transmissions are resolved by adding a single equation 4 . Further, the authors in [17] have shown that the avalanche point happens at the same time slot for both T I (m) and F R (m) most of the time. In addition, after the avalanche point, resolving the users' packets happens very slowly causing only marginal increment in T I (m) and F R (m).…”
Section: System Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…This comes from the inherent nature of SIC where suddenly a large number of users' transmissions are resolved by adding a single equation 4 . Further, the authors in [17] have shown that the avalanche point happens at the same time slot for both T I (m) and F R (m) most of the time. In addition, after the avalanche point, resolving the users' packets happens very slowly causing only marginal increment in T I (m) and F R (m).…”
Section: System Modelmentioning
confidence: 99%
“…Andor-tree evaluations [16] of the frameless slotted ALOHA in [17] show that T I (m) and F R (m) both have an avalanche behavior versus the number of elapsed time slots. That is, a sudden jump from a low value to a much higher value is observed at a specific time slot.…”
Section: System Modelmentioning
confidence: 99%
See 3 more Smart Citations